Clinical and radiographic evaluation of implant‐supported single‐unit crowns with cantilever extension in posterior areas: A retrospective study with a follow‐up of at least 10 years. (15th January 2021) - Schmid, Eric; Roccuzzo, Andrea; Morandini, Michele; Ramseier, Christoph A.; Sculean, Anton; Salvi, Giovanni E.
Abstract: Background: Implant‐supported restorations with cantilever extension may display high rates of biological and technical complications. Purpose: To report the outcomes of single‐unit crowns with cantilever extension (SCCs). Materials and methods: Patients with SCCs were reevaluated after ≥10 years of loading. Radiographic marginal bone levels (mBLs) at baseline (ie, delivery of SCCs) and follow‐up were calculated and compared between implant surfaces adjacent to and distant from the cantilever extension. Implant survival and success rates were calculated. Results: Twenty‐one patients with 25 SCs supported by 25 implants were reevaluated after a mean of 13.6 ± 3.8 years (range: 10–19 years). No implants were lost. The mean overall mBLs changed from 0.99 mm ± 0.95 at baseline to 0.95 mm ± 0.99 at follow‐up ( p = 0.853). The mean pocket probing depths changed from 3.39 mm ± 0.62 at baseline to 3.34 mm ± 0.54 at follow‐up ( p = 0.635). Loss of retention occurred 3× in 2 patients (14.3%). At follow‐up, peri‐implant health was diagnosed in 10 (48%) and peri‐implant mucositis in 11 (52%) patients, respectively. Conclusions: Within the limitations of the present study, the use of implant‐supported SCs with cantilever extension in posterior areas represents a reliable long‐term treatment option with a 100% implant survival rate and minimal marginal bone level changes.